Front Cover: Kinase Sensing Based on Protein Interactions at the Catalytic Site (Chem. Eur. J. 17/2022). Issue 17 (14th March 2022) - Solomon, Ohad; Sapir, Hannah; Mervinetsky, Evgeniy; Chen, Yu‐Ju; Friedler, Assaf; Yitzchaik, Shlomo
Abstract : An electrochemical biosensor has been developed that is based on the interaction between the catalytic site of the kinase and the phosphorylation site of its substrate for detection. We adsorbed the phosphorylation site peptide of HDGF, a substrate of ERK2, on gold electrodes and were able to electrochemically sense ERK2 without ATP. Surface chemistry analysis showed that ERK2 was bound to the peptide monolayer, which changed the packing of the layer, resulting in increased permeability of redox‐active species through the layer and electrochemical sensing. More information can be found in the Research Article by A. Friedler, S. Yitzchaik et al. (DOI: 10.1002/chem.202104227 ).